Schemes of Funding Music Research in Italy: A Case Study in Comparison with other European Countries - Carolyn Gianturco (Humanities, 2015)
The awareness of the central government and other supportive agencies in Italy as to the need for research to be accomplished in music and music history in that country is determined by first stating what that support has been for such research in the 1990s, together with its accessibility to groups and/or individuals working in that field, and then reporting how such aid has been reduced in the more recent times of financial crises. In order to assess Italy’s position not in isolation but more realistically by considering it within a broader geographical frame, the same investigation has been accomplished for a group of other culturally developed countries in Europe which offer sufficient areas of comparison: Spain, France, England, Germany. Sadly, Italy does not come off well. Perhaps surprisingly but still sadly this is shown not to be due to the present financial crises but to a long-standing absence of respect for the entire musical history of the country and for the need that it be known and understood thoroughly. In short, the government in Italy seems not to have been sufficiently aware of its responsibility to acknowledge and preserve its musical patrimony by adequately supporting research which aims at uncovering the country’s rich past, understanding it, and thereby making it available to professional performing musicians and, through them, also to the people of Italy and the rest of the world.